"Pure apathy" and cognitive dysfunctions in Parkinson's disease: A meta-analytic study. (November 2018) - D'Iorio, Alfonsina; Maggi, Gianpaolo; Vitale, Carmine; Trojano, Luigi; Santangelo, Gabriella
Highlights: In Parkinson's disease (PD), apathy is associated with more severe cognitive deficits. Apathetic PD patients showed more severe executive dysfunctions. Apathetic and non-apathetic PD patients did not differ on short term verbal memory. Pure apathy is related to reduced long term verbal memory and visuospatial abilities. Pure apathy is strongly related to inhibition dysfunctioning in PD. Abstract: Parkinson's Disease (PD) is characterized by motor and non-motor symptoms such as cognitive deficit and behavioural disturbances. Apathy seems to be related to cognitive impairment, but some studies failed to confirm the relationship due to different methodological procedures across studies. A meta-analysis on 8 studies was performed to explore the cognitive correlates of apathy without depression and dementia (pure apathy). Global cognitive function, memory, executive functions, processing speed/attention/working memory, visuospatial abilities and language were the outcomes. The effect size of the relationship between "pure apathy" and reduced global cognitive functioning, executive functions, processing speed/attention/working memory, visuospatial functions, long-term verbal memory was moderate, whereas apathy was strongly associated with inhibition dysfunctioning. Our results revealed a strong association between "pure apathy" and cognitive dysfunctions, particularly deficit of memory and executive functions related to altered prefronto-subcortical circuitries.